Evaluation of Brawijaya University’s Interior Physical Environment Effect on Library Users’ Comfort - Debri Haryndia Putri (Program Pendidikan Vokasi Universitas Brawijaya, 2016)
A space affects humans not physically but also psychologically. Therefore, we are often familiar with the term